Treasury Richness - FLECKENSTEIN, MATTHIAS; LONGSTAFF, FRANCIS A. (Journal of Finance, 2024)
ABSTRACT We provide estimates of Treasury convenience premia across the entire term structure of Treasury bills, notes, and bonds over more than a quarter of a century and document a variety of key stylized facts about their time‐series and cross‐sectional patterns. These results raise concerns about the evolving nature of Treasury markets and suggest that investors may now place less weight on the traditional role of Treasury securities as liquid trading vehicles. These stylized facts provide empirical benchmarks that could help guide future theoretical and empirical work about the economics of safe assets in financial markets.